A ZIF-67 resin composite adsorbent based on oxide seeds, preparation method and application

By growing oxide seeds through hydrothermal reaction in the resin, ZIF-67-carried resin composite adsorbent was prepared, and the problems of low concentration phosphate removal rate and low metal utilization rate in the prior art were solved, and efficient, stable and economical phosphate removal effect was achieved.

CN116532095BActive Publication Date: 2025-04-18NANJING NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210093364.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2025-04-18
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

The prior art has problems such as low removal rate, high cost, low loading of metal nanoparticles and low utilization rate when treating low concentrations of phosphates in water, especially when the coexisting ions are present, the performance is disturbed.

Method used

By growing oxide seeds in situ in hydrothermal reaction, a composite adsorbent is prepared with ZIF-67 resin, and the ion exchange and adsorption properties of the resin are used to combine with ZIF-67 materials loaded into the resin pores, improving the low-concentration phosphorus removal effect and metal utilization rate.

Benefits of technology

It realizes efficient removal of low-concentration phosphates in water, improves metal utilization, material stability and recycling performance, and reduces production and use costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116532095B_ABST
    Figure CN116532095B_ABST
Patent Text Reader

Abstract

The present invention discloses a ZIF-67 resin composite adsorbent based on oxide seeds, a preparation method and an application. The composite adsorbent described in the present invention is resin D201 loaded with ZIF-67 particles; the X-ray diffraction pattern of the composite adsorbent has diffraction peaks at the following 2θ angles: 7.31, 10.36, 12.72, 14.40, 16.45, 18.04. The present invention solves the problems of large steric hindrance of metal ions entering the pores, low loading of MOF components, large amounts of aggregation on the outer surface of the resin, and easy peeling of MOFs during use during the preparation of resin-MOF adsorbents. In the present invention, ZIF-67 is grown in situ based on hydrated cobalt oxide seeds, with resin D201 as a carrier, and then converted into ZIF-67 to obtain a composite adsorbent. The present invention prepares the ZIF-67 adsorbent material through metal oxides, achieves a significant increase in the loading amount of ZIF-67 on the resin, and improves the phosphorus removal capacity and recycling performance. It has the characteristics of high removal efficiency of low-concentration phosphate, high mechanical strength of the composite material, and high resistance to coexisting ion interference, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic-organic composite material synthesis, and particularly relates to an oxide seed-based ZIF-67 resin composite adsorbent, a preparation method and an application thereof. Background Art

[0002] The discharge of phosphates causes pollution problems such as eutrophication of water bodies, which seriously affects the ecological balance and drinking water safety. The actual phosphorus content in water bodies is usually not high. The current treatment of phosphates in water faces the problem of controlling low-concentration phosphorus. There are many types of phosphorus removal adsorbents. Some have a high saturated adsorption capacity, but the removal rate for low-concentration phosphorus is not high, such as activated carbon; some have excellent phosphorus removal performance, but the production cost or use cost is very high, such as nano lanthanum oxide. In the actual treatment of phosphorus-containing wastewater, the presence of coexisting ions of phosphates such as sulfate and chloride in the water body will interfere with the performance of phosphorus removal adsorbents based on ion exchange or charge action. Therefore, there is a real social need for effective adsorbents to remove low-concentration phosphates in water.

[0003] Metal organic frameworks (MOFs) are a new type of porous material composed of inorganic metal ions and organic ligands. It has the advantages of large surface area, high porosity, easy functionalization, and good water stability. At the same time, MOFs are widely used as adsorbents and show good adsorption performance. However, in practical applications, the main challenge of using MOFs as adsorbents is its powdery morphology, that is, its disadvantages are weak recyclability, complex operation process, and possible secondary pollution. MOF has been reported as a phosphorus removal adsorbent. At 298K, the maximum adsorption capacity of Ce-BDC is greater than 179mg P / g, and there is no significant change in the pH range of 3-11. At the same time, interfering ions have little effect on the phosphorus removal ability of Ce-BDC, and it has strong selectivity for phosphate. Compounding MOF materials with other materials can not only obtain a stable protective effect, but also synergize with the groups of the substrate to achieve more efficient and unique adsorption performance. For example, a Chinese patent with a Chinese authorization number of CN110523395B and an authorization publication date of October 29, 2021 discloses a resin-loaded ZIF-67 adsorbent and a preparation method thereof. The method utilizes an alternating deposition method to first fix the ligand on the resin, then add a cobalt salt, and perform a complexation reaction to obtain a resin-loaded ZIF-67 adsorbent. The resin-loaded ZIF-67 adsorbent prepared by this method has good low-concentration selective phosphorus removal capability. However, the composite adsorbent ZIF-67 prepared by this method has a small loading amount, a limited phosphate adsorption amount, and a slight decrease in phosphorus removal efficiency when recycled.

[0004] Adsorption resins are widely used in the removal of phosphate pollution. Resin materials have large specific surface area, high mechanical strength, are easy to separate from water bodies, and have good regeneration performance. However, the effective groups of these adsorption resins are all positively charged, which will have a great steric hindrance when metal ions diffuse into the pores. The relevant literature reported on resin-loaded MOF materials shows that MOFs are basically concentrated on the surface of the resin, and the loading amount is very small. Effectively loading MOFs into the resin pores, so that the MOFs material and the carrier resin can play a synergistic role in adsorption and phosphorus removal, and further improve the adsorption performance of the material, is now a hot topic in the research of inorganic resin composite adsorbents. Summary of the invention

[0005] Purpose of the invention: The present invention provides a ZIF-67 resin composite adsorbent based on oxide seeds, a preparation method and an application. The present invention obtains a ZIF-67 resin composite adsorbent by in-situ growth of oxide seeds in a hydrothermal reaction. The present invention combines the ion exchange and adsorption properties of the resin itself with the ZIF-67 material loaded into the resin pores, and has the characteristics of good low-concentration phosphorus removal effect, high metal utilization rate and excellent stability, and can be efficiently reused. The present invention solves the problems of low metal nanoparticle loading, low metal utilization rate and surface peeling during use in organic-inorganic composite phosphorus removal adsorption materials in the prior art.

[0006] Technical solution: The present invention discloses a ZIF-67 resin composite adsorbent based on oxide seeds, wherein the composite adsorbent is resin D201 loaded with ZIF-67 particles; the X-ray diffraction pattern of the composite adsorbent has diffraction peaks at the following 2θ angles: 7.31, 10.36, 12.72, 14.40, 16.45, and 18.04.

[0007] As a preferred embodiment of the present invention, the cobalt content of the composite adsorbent is 7.15-13.82% of the total mass of the composite adsorbent; and the particle size of the ZIF-67 is 20nm-250nm.

[0008] As a preferred embodiment of the present invention, the composite adsorbent described in the present invention is prepared by the following method: adding cobalt nitrate hexahydrate and macroporous resin D201 to an alcohol aqueous solution to obtain a resin material with a high load of cobalt salt, then filtering out the resin material loaded with cobalt salt, and drying it in an oven at a constant temperature; preparing a sodium hydroxide aqueous solution, adding the dried resin to the sodium hydroxide solution and stirring; filtering out the resin with a high load of hydrated cobalt oxide, and washing it to neutrality; finally, adding the washed resin and a ligand dimethylimidazole DMF solution to a tetrafluoroethylene reactor, and reacting at a constant temperature to obtain a ZIF-67 loaded resin composite adsorbent.

[0009] The present invention adopts an oxide seed template method, and adjusts the ZIF-67 nanoparticles from direct in-situ preparation to first loading oxides in the pores of the resin material, and then converting the oxides into ZIF-67 nanoparticles, so that the loading amount of ZIF-67 is almost equivalent to that of the oxides, avoiding the problem of too small loading amount caused by pore steric hindrance. At the same time, when the oxides are gradually converted into ZIF-67, ZIF-67 has very good dispersibility, and the formed new material has a multi-gradient pore structure, which significantly improves the efficiency of ZIF-67 materials in application under the new preparation technology.

[0010] From the reaction principle of the present invention, it can be seen that ZIF-67 in the present invention is based on the in-situ growth of hydrated cobalt oxide seeds, with resin D201 as a carrier, and then converted into ZIF-67 to obtain a composite adsorbent, that is, the resin of the present invention is used as a carrier to first fix the hydrated oxide of cobalt as a seed, and suitable reaction conditions drive the ligand to react with the oxide in the resin pores to obtain the ZIF-67-loaded resin adsorbent, and the resin must have a cationic active group for fixing the hydrated oxide. The resin selected by the present invention is a macroporous ion exchange resin D201 with a cross-linked polystyrene skeleton, and the D201 resin has a positively charged quaternary amine group.

[0011] As a preferred embodiment of the present invention, the composite adsorbent is prepared by the following method:

[0012] (1) dissolving cobalt nitrate hexahydrate in a solvent, adding D201 resin to the solution and stirring, filtering out the resin and drying it; the solvent is a mixed solution of alcohol and water;

[0013] (2) preparing a sodium hydroxide aqueous solution, adding the D201 resin loaded with cobalt salt in step (1) to the sodium hydroxide aqueous solution, stirring, filtering and washing with water until neutral;

[0014] (3) The D201 resin loaded with hydrated cobalt oxide is transferred to a reaction kettle, dimethylimidazole and DMF solution are added, and a constant temperature hydrothermal reaction is carried out at 80-140° C. for 12-24 hours. The resin after the reaction is washed and dried to obtain a ZIF-67 loaded resin composite adsorbent.

[0015] As a preferred embodiment of the present invention, in step (1), the solvent is a mixed solution of water, methanol and ethanol in a volume ratio.

[0016] As a preferred embodiment of the present invention, in step (1), the solvent is a mixed solution of water, methanol and ethanol in a volume ratio of 1:1:1.

[0017] As a preferred embodiment of the present invention, in step (1), the mass ratio of cobalt nitrate hexahydrate to D201 resin is 2-10:1.

[0018] As a preferred embodiment of the present invention, in step (1), the mass ratio of cobalt nitrate hexahydrate to D201 resin is 2-5:1.

[0019] As a preferred embodiment of the present invention, in step (1), the mass ratio of the cobalt nitrate hexahydrate to the D201 resin is 2:1.

[0020] As a preferred embodiment of the present invention, in step (1), the stirring time is 12-24 hours (magnetic rotation speed is 60-80 r / min), and the drying temperature is 50°C-80°C.

[0021] As a preferred embodiment of the present invention, in step (2), the mass percentage concentration of the sodium hydroxide aqueous solution is 5-15%wt.

[0022] As a preferred embodiment of the present invention, in step (2), the stirring time is 12-24 hours (magnetic rotation speed is 60-80 r / min).

[0023] As a preferred embodiment of the present invention, in step (3), the drying temperature is 50°C-80°C.

[0024] As a preferred embodiment of the present invention, in step (3), the washing is performed by washing with water until neutrality, and then washing with ethanol.

[0025] As a preferred embodiment of the present invention, the mass ratio of the D201 resin to dimethylimidazole is 1:2-10.

[0026] As a preferred embodiment of the present invention, the mass ratio of the D201 resin to dimethylimidazole is 1:2-5.

[0027] As a preferred embodiment of the present invention, the mass ratio of the D201 resin to dimethylimidazole is 1:2.

[0028] As a preferred embodiment of the present invention, the mass ratio of the D201 resin to dimethylimidazole is 1:2.

[0029] The method for preparing the ZIF-67 resin composite adsorbent based on oxide seeds of the present invention comprises the following steps:

[0030] (S1) dissolving cobalt nitrate hexahydrate in a solvent, adding D201 resin to the solution and stirring, filtering out the resin and drying it; the solvent is a mixed solution of water, methanol and ethanol;

[0031] (S2) preparing a sodium hydroxide aqueous solution, adding the D201 resin loaded with cobalt salt in step (1) to the sodium hydroxide aqueous solution, stirring, filtering and washing with water until neutral;

[0032] (S3) The D201 resin loaded with hydrated cobalt oxide is transferred to a reaction vessel, dimethylimidazole and DMF solution are added, and a constant temperature hydrothermal reaction is carried out at 80-140° C. for 12-24 hours. The resin after the reaction is washed and dried to obtain a ZIF-67 loaded resin composite adsorbent.

[0033] As a preferred embodiment of the present invention, in step (S1), the mass ratio of the cobalt nitrate hexahydrate to the solvent is 1:5-10.

[0034] The invention discloses an application of the oxide seed-based ZIF-67 resin composite adsorbent in phosphorus removal.

[0035] Beneficial effects: (1) In the present invention, the metal oxide is introduced into the resin pores by using an alcohol aqueous solution and sodium hydroxide and by changing the solvent in the preparation step. The defect that the metal salt cannot efficiently participate in the hydrothermal reaction in the prior art is solved by structural transformation, so as to achieve sufficient immobilization of MOF in the resin pores; (2) The present invention adopts a new method of growing MOFs using oxide seeds as templates. After using resin materials to fix hydrated cobalt oxide, Co is transformed from an oxide structure to a MOF structure through a hydrothermal reaction, so that the metal can fully coordinate with the ligand dimethylimidazole inside the pores of the resin beads to form ZIF-67 fixation. Compared with the reported mixing method and alternating deposition method, the ions in the oxide are not dissipated into the reaction solution, and a ZIF-67 / resin composite adsorbent with a high MOF loading can be prepared; (3) The present invention grows ZIF-67 inside a macroporous resin. Compared with the reported methods, there is no Due to the spatial steric hindrance of the pores, MOF no longer accumulates in large quantities on the resin surface and will not easily peel off from the resin when used, which greatly improves the recycling performance of the composite adsorbent; (4) During the reaction process of the present invention, Co in the oxide gradually forms a new structure in the hydrothermal reaction, so that the ZIF-67 obtained in this way has good dispersion in the resin pores, the utilization rate of the metal is greatly improved, and the nanomaterial can fully contact with the phosphate in the water body. Therefore, the composite adsorbent has a better removal efficiency for low-concentration phosphates and enhances the selectivity for phosphate; (5) The preparation method of the composite adsorbent of the present invention can make ZIF-67 distributed in the pores of the porous resin, has excellent acid and alkali resistance and stability, and does not dissolve in a wide pH range; (6) The preparation method of the composite adsorbent of the present invention is simple to operate, has a high raw material utilization rate, is suitable for large-scale industrial production, and is an economical and efficient adsorbent preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image of the composite adsorbent prepared in Example 2;

[0037] Figure 2The XRD spectrum of the ZIF-67-loaded resin (ZIF-67@D201-1) composite adsorbent synthesized in Example 1;

[0038] Figure 3 The XRD spectrum of the ZIF-67-loaded resin (ZIF-67@D201-2) composite adsorbent synthesized in Example 2;

[0039] Figure 4 The XRD spectrum of the ZIF-67-loaded resin (ZIF-67@D201-3) composite adsorbent synthesized in Example 3;

[0040] Figure 5 The XRD spectrum of the ZIF-67-loaded resin (ZIF-67@D201-4) composite adsorbent synthesized in Example 4;

[0041] Figure 6 The XRD spectrum of the ZIF-67-loaded resin (ZIF-67@D201-5) composite adsorbent synthesized in Example 5;

[0042] Figure 7 This is a diagram showing the adsorption effect of the ZIF-67 resin composite adsorbent of Examples 1-5 on low concentration phosphate;

[0043] Figure 8 This is a diagram showing the recycling efficiency of the ZIF-67 resin (ZIF-67@D201-2) composite adsorbent synthesized in Example 2. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments.

[0045] Example 1: Preparation of ZIF-67 resin composite adsorbent based on oxide seeds

[0046] (1) Weigh 2 g of cobalt nitrate hexahydrate into a beaker, add 10 mL of water, methanol, and ethanol (volume ratio 1:1:1) to fully dissolve, add 1 g of D201 resin into the solution and stir for 12 hours (magnetic speed at 80 r / min), filter out the resin and dry it in a thermostat at 80°C for 12 hours;

[0047] (2) Prepare a 10% wt sodium hydroxide aqueous solution (sodium hydroxide solution immerses the resin, the same below), add the D201 resin loaded with cobalt salt into the solution and stir for 12 hours (magnetic rotation speed is 80 r / min), filter out and wash with water until neutral;

[0048] (3) The D201 resin loaded with hydrated cobalt oxide was transferred to a 50 mL tetrafluoroethylene reactor, 2 g of dimethylimidazole and 20 mL of DMF solution were added, and the reaction was carried out at a constant temperature of 80° C. for 12 hours.

[0049] (4) Filter out the resin particles, wash with water until neutral, wash with ethanol, and dry in a constant temperature oven at 80° C. for 12 hours to obtain the ZIF-67-loaded resin adsorbent ZIF-67@D201-1.

[0050] result:

[0051] Figure 2 The XRD spectrum of the ZIF-67 resin composite adsorbent ZIF-67@D201-1 synthesized in this example. Figure 1 In the figure, 2θ=7.31, 10.36, 12.72, 14.40, 16.45, and 18.04 are the characteristic peaks of ZIF-67, which proves that ZIF-67@D201-1 was successfully prepared. The cobalt content of the composite adsorbent is 13.82% by mass according to ICP detection.

[0052] Under the preparation conditions of Example 1, the mass ratio of D201 to cobalt nitrate hexahydrate is adjusted from 1:2 to 1:10, or the mass ratio of D201 resin to dimethylimidazole is adjusted from 1:2 to 1:10, or the stirring speed is adjusted from 60-80r / min, the stirring time, etc., to obtain a ZIF-67 resin composite adsorbent with the same performance as prepared in Example 1.

[0053] Example 2: Preparation of ZIF-67 resin composite adsorbent based on oxide seeds

[0054] The ZIF-67 resin composite adsorbent prepared in this example has the same reactants as those described in Example 1, and the temperature in the hydrothermal reaction is changed. The specific method is as follows:

[0055] (1) Weigh 2 g of cobalt nitrate hexahydrate into a beaker, add 10 mL of water, methanol, and ethanol (volume ratio 1:1:1) to fully dissolve, add 1 g of D201 resin into the solution and stir for 12 hours (magnetic speed at 80 r / min), filter out the resin and dry it in a thermostat at 80°C for 12 hours;

[0056] (2) Prepare a 10% wt sodium hydroxide aqueous solution, add the D201 resin loaded with cobalt salt into the solution and stir for 12 hours (magnetic rotation speed is 80 r / min), filter and wash with water until neutral;

[0057] (3) The D201 resin loaded with hydrated cobalt oxide was transferred to a 50 mL tetrafluoroethylene reactor, 2 g of dimethylimidazole and 20 mL of DMF solution were added, and the mixture was subjected to a hydrothermal reaction at 100° C. for 12 hours.

[0058] (4) Filter out the resin particles, wash with water until neutral, wash with ethanol, and dry in a constant temperature oven at 80° C. for 12 hours to obtain the ZIF-67-loaded resin adsorbent ZIF-67@D201-2.

[0059] result:

[0060] Figure 3 is the XRD spectrum of the ZIF-67-loaded resin composite adsorbent ZIF-67@D201-2 synthesized in this example, Figure 1 is a scanning electron microscope image of the ZIF-67 resin composite adsorbent prepared in this example. Figure 2 Among them, 2θ=7.31, 10.36, 12.72, 14.40, 16.45, and 18.04 are the characteristic peaks of ZIF-67, which proves that ZIF-67@D201-2 was successfully prepared. The cobalt content of the composite adsorbent is 12.74% by mass according to ICP detection.

[0061] Under the preparation conditions of Example 2, the mass ratio of D201 to cobalt nitrate hexahydrate is adjusted from 1:2 to 1:10, or the mass ratio of D201 resin to dimethylimidazole is adjusted from 1:2 to 1:10, or the stirring speed is adjusted from 60-80r / min, the stirring time, etc., to obtain a ZIF-67 resin composite adsorbent with the same performance as prepared in Example 2.

[0062] Example 3: Preparation of ZIF-67 resin composite adsorbent based on oxide seeds

[0063] The ZIF-67 resin composite adsorbent prepared in this example has the same reactants as those described in Example 1, and the reaction temperature is changed. The specific method is as follows:

[0064] (1) Weigh 2 g of cobalt nitrate hexahydrate into a beaker, add 10 mL of water, methanol, and ethanol (volume ratio 1:1:1) to fully dissolve, add 1 g of D201 resin into the solution and stir for 12 hours (magnetic speed at 80 r / min), filter out the resin and dry it in a thermostat at 80°C for 12 hours;

[0065] (2) Prepare a 10% wt sodium hydroxide aqueous solution, add the D201 resin loaded with cobalt salt into the solution and stir for 12 hours (magnetic rotation speed is 80 r / min), filter and wash with water until neutral;

[0066] (3) The D201 resin loaded with hydrated cobalt oxide was transferred to a 50 mL tetrafluoroethylene reactor, 2 g of dimethylimidazole and 20 mL of DMF solution were added, and the reaction was carried out at a constant temperature of 120° C. for 12 hours.

[0067] (4) Filter out the resin particles, wash with water until neutral, wash with ethanol, and dry in a constant temperature oven at 80° C. for 12 hours to obtain the ZIF-67-loaded resin adsorbent ZIF-67@D201-3.

[0068] result:

[0069] Figure 4 The XRD spectrum of the ZIF-67 resin composite adsorbent ZIF-67@D201-3 synthesized in this example. Figure 3 Among them, 2θ=7.31, 10.36, 12.72, 14.40, 16.45, and 18.04 are the characteristic peaks of ZIF-67, which proves that ZIF-67@D201-3 was successfully prepared. The cobalt content of the composite adsorbent is 12.32% by mass according to ICP detection.

[0070] Under the preparation conditions of Example 3, the mass ratio of D201 to cobalt nitrate hexahydrate is adjusted from 1:2 to 1:10, or the mass ratio of D201 resin to dimethylimidazole is adjusted from 1:2 to 1:10, or the stirring speed is adjusted from 60-80r / min, the stirring time, etc., to obtain a ZIF-67 resin composite adsorbent with the same performance as prepared in Example 3.

[0071] Example 4: Preparation of MOF-loaded resin composite adsorbent

[0072] The ZIF-67 resin composite adsorbent prepared in this example has the same reactants as those described in Example 1, except that the steps in the synthesis method are changed. The specific method is as follows:

[0073] (1) Weigh 2 g of cobalt nitrate hexahydrate into a beaker, add 10 mL of water, methanol, and ethanol (volume ratio 1:1:1) to fully dissolve, add 1 g of D201 resin into the solution and stir for 12 hours (magnetic speed at 80 r / min), filter out the resin and dry it in a thermostat at 80°C for 12 hours;

[0074] (2) The D201 resin loaded with cobalt salt was transferred to a 50 mL tetrafluoroethylene reactor, 2 g of dimethylimidazole and 20 mL of DMF solution were added, and the mixture was subjected to a hydrothermal reaction at 100° C. for 12 hours.

[0075] (3) Filter out the resin particles, wash with water until neutral, wash with ethanol, and dry in a constant temperature oven at 80° C. for 12 hours to obtain the ZIF-67-loaded resin adsorbent ZIF-67@D201-4.

[0076] result:

[0077] Figure 5 The XRD spectrum of the composite adsorbent ZIF-67@D201-3 synthesized in this example. Figure 4 There is no characteristic peak of ZIF-67 in the XRD spectrum, indicating that the resin-loaded ZIF-67 was not successfully prepared. There is no obvious characteristic peak of oxide in the XRD spectrum, indicating that without the precipitation of sodium hydroxide solution, the resin pores and surface cannot form seeds sufficient to grow ZIF-67. The cobalt content of the composite adsorbent is 0.63% by mass according to ICP detection.

[0078] Example 5: Preparation of ZIF-67 resin composite adsorbent based on oxide seeds

[0079] The ZIF-67 resin composite adsorbent prepared in this example has the same reactants as those described in Example 1, except that the steps in the synthesis method are changed. The specific method is as follows:

[0080] (1) Weigh 2 g of cobalt nitrate hexahydrate into a beaker, add 10 mL of water, methanol, and ethanol (volume ratio 1:1:1) to fully dissolve, add 1 g of D201 resin into the solution, stir for 12 hours (magnetic spindle speed at 80 r / min), and filter out;

[0081] (2) Prepare a 10% wt sodium hydroxide aqueous solution, add the filtered D201 resin into the solution and stir for 12 hours (magnetic speed at 80 r / min), and then wash the filtered water until it is neutral;

[0082] (3) The D201 resin loaded with hydrated cobalt oxide was transferred to a 50 mL tetrafluoroethylene reactor, 2 g of dimethylimidazole and 20 mL of DMF solution were added, and the reaction was carried out at a constant temperature of 120° C. for 12 hours.

[0083] (4) Filter out the resin particles, wash with water until neutral, wash with ethanol, and dry in a constant temperature oven at 80° C. for 12 hours to obtain the ZIF-67-loaded resin adsorbent ZIF-67@D201-5.

[0084] result:

[0085] Figure 6 The XRD spectrum of the ZIF-67 resin composite adsorbent ZIF-67@D201-3 synthesized in this example. Figure 3 Among them, 2θ=7.31, 10.36, 12.72, 14.40, 16.45, and 18.04 are the characteristic peaks of ZIF-67, which proves that ZIF-67@D201-5 was successfully prepared. The cobalt content of the composite adsorbent is 7.15% by mass according to ICP detection.

[0086] Under the preparation conditions of Example 5, the mass ratio of D201 to cobalt nitrate hexahydrate is adjusted from 1:2 to 1:10, or the mass ratio of D201 resin to dimethylimidazole is adjusted from 1:2 to 1:10, or the stirring speed is adjusted from 60-80r / min, the stirring time, etc., to obtain a ZIF-67 resin composite adsorbent with the same performance as prepared in Example 5.

[0087] Embodiment 6:

[0088] In order to demonstrate the high removal ability of the ZIF-67 resin composite adsorbent for low-concentration phosphorus, a static adsorption experiment can be conducted to investigate the phosphate removal effect of the adsorbent. The specific experimental steps are as follows:

[0089] In each 150 mL conical flask, 50 mg of the ZIF-67 resin composite adsorbent prepared in Examples 1-5 was added. A series of 100 mL phosphorus-containing solutions were prepared, with an initial phosphorus concentration of 2 mg / L and interfering ions SO4 2- , Cl - and HCO3 - The concentrations of the samples were 5 mg / L, and then placed in a shaker at 25°C for 12 hours. Figure 7 The horizontal axes 1-5 represent the adsorbents prepared in Examples 1-5, respectively. The adsorbent ZIF-67@D201- in Example 2 has a very good removal efficiency for low-concentration phosphate in water. 2- , Cl - and HCO3 - Under competitive conditions, the phosphate removal rates can reach 95.3%, 85.3%, 93.7% and 92.3% respectively.

[0090] Embodiment 7:

[0091] In order to demonstrate the recycling ability of the ZIF-67-loaded resin composite adsorbent, a static adsorption-desorption cycle experiment can be conducted. The specific experimental steps are as follows:

[0092] Prepare 100mL of phosphorus-containing solution with an initial phosphorus concentration of 2mg / L. Add 0.5g / L of adsorbent ZIF-67@D201-2, and then place it in a shaker at 25℃ for 12 hours. Prepare 2mmol / L sodium hydroxide 2% NaCl mixed desorption solution, add the adsorbed ZIF-67@D201-2, and place it in a shaker at 25℃ for 12 hours. Wash with water until neutral, and use the adsorbent again. Perform 6 cycles in sequence and record the relevant results. The results are as follows Figure 8 After 6 cycles, ZIF-67@D201-2 still maintains a high efficiency of 91.1% in removing low-concentration phosphorus.

[0093] Embodiment 8:

[0094] In order to demonstrate the engineering practicability of the ZIF-67 resin composite adsorbent synthesized by the new method, the processing capacity and stability of the material can be examined by column adsorption experiment. The specific experimental steps are as follows:

[0095] Configure simulated low-concentration phosphorus-containing wastewater, the initial phosphorus concentration is 2 mg / L, and the interfering ion is SO4 2- , Cl - and HCO3 - , each is 5 mg / L. The dosage of ZIF-67-loaded resin adsorbent ZIF-67@D201-2 is 5 cm 3 , the speed is 5-20min / BV. Under the premise that the effluent phosphorus concentration is lower than 0.5mg / L, the treatment capacity of ZIF-67@D201-2 adsorbent is 1730-2990BV.

Claims

1. A ZIF-67 resin composite adsorbent based on oxide seeds, characterized in that: The oxide seed is hydrated cobalt oxide; the composite adsorbent is resin D201 loaded with ZIF-67 particles; the XRD diffraction pattern of the composite adsorbent has diffraction peaks at the following 2θ angles: 7.31, 10.36, 12.72, 14.40, 16.45, 18.04, and the cobalt content thereof accounts for 12.32%-13.82% of the total mass of the composite adsorbent; the ZIF-67 particle size is 20nm-250nm; and the composite adsorbent is prepared by the following method: (1) dissolving cobalt nitrate hexahydrate in a solvent, adding D201 resin to the solution and stirring, filtering out the resin and drying it; the solvent is a mixed solution of alcohol and water; (2) preparing a sodium hydroxide aqueous solution, adding the D201 resin loaded with cobalt salt in step (1) to the sodium hydroxide aqueous solution, stirring, filtering and washing with water until neutral; (3) The D201 resin loaded with hydrated cobalt oxide is transferred to a reaction kettle, dimethylimidazole and DMF solution are added, and a constant temperature hydrothermal reaction is carried out at 80-140° C. for 12-24 hours. The resin after the reaction is washed and dried to obtain a ZIF-67 loaded resin composite adsorbent.

2. The ZIF-67 resin composite adsorbent based on oxide seeds according to claim 1, characterized in that: In step (1), the mass ratio of the cobalt nitrate hexahydrate to the solvent is 1:5-10.

3. The ZIF-67 resin composite adsorbent based on oxide seeds according to claim 1, characterized in that: In step (1), the solvent is a mixed solution of water, methanol and ethanol.

4. The ZIF-67 resin composite adsorbent based on oxide seeds according to claim 1, characterized in that: In step (1), the mass ratio of the cobalt nitrate hexahydrate to the D201 resin is 2-10:

1.

5. The ZIF-67 resin composite adsorbent based on oxide seeds according to claim 1, characterized in that: In step (2), the mass percentage concentration of the sodium hydroxide aqueous solution is 5-15%wt.

6. The ZIF-67 resin composite adsorbent based on oxide seeds according to claim 1, characterized in that: The mass ratio of the D201 resin to dimethylimidazole is 1:2-5.

7. Use of the oxide seed-based ZIF-67 resin composite adsorbent as claimed in claim 1 in phosphorus removal.

Citation Information

Patent Citations

  • A MOF-supported resin composite adsorbent, its preparation method and application

    CN110523395B

  • Nanometer composite fiber membrane and preparation method thereof

    CN108951158A

  • MOF-loaded resin composite adsorbent as well as preparation method and application thereof

    CN110523395A